THE IMPACT OF INTENSIVE GROWTH STRATEGY ON LEADERSHIP STYLE AND SUCCESSFUL SELLING OF PREMIUM BRAND CAR DEALERS - Thongsook ularn, Sookchok (Strategic Perspectives on Business and Marketing Management, 2023)
The objectives of this quality research were: 1) to explore the most successful intensive strategy enhancing the sales of car dealers in the views of experienced executives, 2) to look into the reasons underlying that successful strategy, 3) to study the impact from the strategy to the leadership styles: telling, selling, participating, and delegating styles, and 4) to study the impact from the intensive strategy to the successful leadership behaviors in premium brand car dealers. This research has been conducted by applying an in-depth interview method. Finding found that, firstly, 75% of executives found that the most successful intensive strategy is marketing development; secondly, 80% of executives reasoned for the successful sales that marketing development strategy could be applied to identify lead group in order to obtain the prospect customers who, then, will be delivered to the premium sales standard process; thirdly, 80% of executives have admitted that the growth strategy has given the most impact to telling leadership style, and, finally, in the views of executives, the successful leadership behavior, who focused task-oriented rather than relationship-oriented, was able to drive the organizations to success.